Inside Back Cover: Photosensitization of Singlet Oxygen and In Vivo Photodynamic Therapeutic Effects Mediated by PEGylated W18O49 Nanowires (Angew. Chem. Int. Ed. 47/2013). Issue 47 (4th November 2013) - Kalluru, Poliraju; Vankayala, Raviraj; Chiang, Chi‐Shiun; Hwang, Kuo Chu
<x xml:space="preserve">Abstract</x> W18O49 nanowires can sensitize the formation of singlet oxygen upon irradiation with near‐infrared (NIR) light. In their Communication on page 12332 ff., K. C. Hwang and co‐workers describe the complete destruction of solid tumors in mice by W18O49‐nanowire‐mediated photodynamic therapy (PDT). This effect was not achieved when employing photothermal therapy or the anticancer drug doxorubicin.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>